Tomatidine Improves Pulmonary Inflammation in Mice with Acute Lung Injury. (7th September 2021) - Huang, Wen-Chung; Wu, Shu-Ju; Chen, Ya-Ling; Lin, Chwan-Fwu; Liou, Chian-Jiun
Abstract : Tomatidine, which is isolated from green tomato, can ameliorate inflammation and oxidative stress in cells and animal experiments and has been shown to improve airway inflammation in a murine model of asthma. Here, we investigated whether tomatidine can ameliorate acute lung injury in mice. Mice were given tomatidine by intraperitoneal injection for 7 consecutive days, and then, lung injury was induced via intratracheal instillation of lipopolysaccharide (LPS). Tomatidine reduced inflammatory cytokine expressions in bronchoalveolar lavage fluid (BALF), attenuated neutrophil infiltration in the BALF and lung tissue, increased superoxide dismutase activity and glutathione levels, and alleviated myeloperoxidase expression in the lung tissue of mice with lung injury. Tomatidine also decreased inflammatory cytokine and chemokine gene expression in inflammatory lungs and attenuated the phosphorylation of mitogen-activated protein kinase and nuclear factor kappa B. Furthermore, tomatidine enhanced the production of heme oxygenase-1, decreased the secretion of inflammatory cytokines and chemokines in LPS-stimulated lung epithelial cells, and attenuated THP-1 monocyte adhesion. Our findings suggest that tomatidine attenuates oxidative stress and inflammation, improving acute lung injury in mice.